Evaluación del plan curricular de un programa de posgrado en Ciencias de la Salud. - Amado, José; Rodriguez, Natalia; Oscanoa, Teodoro (Revista Horizonte Médico)
Objective: To evaluate the internal validity of a health sciences graduate program curriculum. Materials and methods: A descriptive study using a documentary analysis of a public university’s Master of Education and Health Research Program. The internal validity was analyzed through the identification of professional profile indicators, subjects’ syllabi were rated, and the congruence in the curriculum map was assessed. Personality (alpha) and occupational (beta) indicators were considered. Descriptive statistics was performed using Microsoft Excel 2013. Results: Alpha indicators such as the ability to design, demonstrate, assess and apply, and beta indicators such as being a leader, researcher, professor and assessor were identified. The syllabi achieved a passing grade, but deficiencies in the methodology, materials and bibliography were observed. The indicators “knowledge”, “application”, “being a researcher and professor” were interrelated in the curriculum map; however, indicators such as “assessment”, “communication”, “being a leader and assessor” were not interrelated. Conclusions: The proposed professional profile is represented in the curriculum, but the indicators are not adequately interrelated.